2013
DOI: 10.1002/cbf.2947
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n‐3 long‐chain polyunsaturated fatty acids modify phosphoenolpyruvate carboxykinase activity and lipid synthesis from glucose in adipose tissue of rats fed a high‐sucrose diet

Abstract: Long-chain polyunsaturated n-3 fatty acids (n-3 LCPUFAs) have hypolipidemic effects and modulate intermediary metabolism to prevent or reverse insulin resistance in a way that is not completely elucidated. Here, effects of these fatty acids on the lipid profile, phosphoenolpyruvate carboxykinase (PEPCK) activity, lipid synthesis from glucose in epididymal adipose tissue (Ep-AT) and liver were investigated. Male rats were fed a high-sucrose diet (SU diet), containing either sunflower oil or a mixture of sunflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, owing to the polarity difference between the analytes and solvents, it was difficult to achieve an exhaustive FFA extraction from samples. Increasing studies reported that choosing some solvent mixtures could increase the FFA and lipid extraction yields , a comparison showed that a chloroform/methanol mixture (2:1, v/v) was the best solvent mixture for FFA extraction . On the basis of these reports, a method of ultrasonic extraction with chloroform/methanol (2:1, v/v) as solvent was carried out to extract FFAs from different organs of pomegranate.…”
Section: Resultsmentioning
confidence: 99%
“…However, owing to the polarity difference between the analytes and solvents, it was difficult to achieve an exhaustive FFA extraction from samples. Increasing studies reported that choosing some solvent mixtures could increase the FFA and lipid extraction yields , a comparison showed that a chloroform/methanol mixture (2:1, v/v) was the best solvent mixture for FFA extraction . On the basis of these reports, a method of ultrasonic extraction with chloroform/methanol (2:1, v/v) as solvent was carried out to extract FFAs from different organs of pomegranate.…”
Section: Resultsmentioning
confidence: 99%